Contamination of Microbial Pathogens and their Antimicrobial Pattern in Operating Theatres of Peri-Urban Eastern Uganda: A Cross-Sectional Study - Matinyi, Sandra; Muwanguzi, Enoch; Akia, Deborah; Byaruhanga, Valentine; Masereka, Edson; Ekeu, Isaac; Atuheire, Collins (BMC infectious diseases, 2018)
Microbial contamination of hospital environment, especially in operating theatres (OT) and other specialized units has greatly contributed to continuous and multiple exposure to nosocomial infections by patients and the public. We purposed to assess microbial contamination of operating theatres and antibacterial sensitivity pattern of bacteria isolated from theatres of Mbale Regional Referral Hospital, Eastern Uganda.
Keywords: Antimicrobial pattern; Operating theatre; Microbial pathogens